Cover Picture: Improvement in Hydrogen Desorption from β‐ and γ‐MgH2 upon Transition‐Metal Doping (ChemPhysChem 12/2015). Issue 12 (24th August 2015) - Hussain, Tanveer; Maark, Tuhina Adit; Chakraborty, Sudip; Ahuja, Rajeev
<x xml:space="preserve">Abstract</x> The thermodynamics and kinetics of hydrogen adsorption and desorption from materials can be enhanced through doping. In their Full Paper Hussain et al. performed a systematic study based on density functional theory to explore the effect of various transition metals as dopants on the hydrogen‐storage properties of the high‐pressure phases (β and γ) of magnesium hydride (MgH2). Upon substituting Mg with small fractions of dopants, the MgH bond strength decreased compared with that of the pure form; this ultimately improves the H2 desorption from these phases of MgH2. More information can be found in the Full paper by T. Hussain et al. on p. 2557.